Integrated method for adaptability and phenotypic stability analysis - doi: 10.4025/actasciagron.v33i2.8272 (Acta Scientiarum. Agronomy, 2011)
The objectives of this study were a description of the Centroid Method, which is used to investigate the phenotypic adaptability of genotypes and the inclusion of new ideotypes therein, creating the Integrated Method for adaptability and phenotypic stability analysis, as well as a comparison of the two methods in a study example. As an applied example of the new proposal, grain yield data of 14 soybean genotypes from experiments at four locations in the state of Minas Gerais were used. In a comparison, the qualitative and quantitative gains of the Centroid Method with seven ideotypes were higher than of the Centroid Method with only four ideotypes for adaptability analysis. With the incorporation of the new ideotypes into the Centroid Method other concepts for the adaptability and phenotypic stability analysis are represented and the modified method was designated “Integrated Method of Adaptability and Stability Analysis”. CS 801 genotype was classified as the genotype with best adaptability to the environments Viçosa, Florestal, São Gotardo and Rio Paranaiba. The stability of the genotypes CAC 1, CS 741, Splendor, UFV 16, UFV 19, UFVP IV-6, UFVP IV-8, UFVP V-15, UFVP V-7, and UFV98700739 was classified as general.